2018
DOI: 10.1371/journal.pone.0202175
|View full text |Cite
|
Sign up to set email alerts
|

Potential of exogenously sourced kinetin in protecting Solanum lycopersicum from NaCl-induced oxidative stress through up-regulation of the antioxidant system, ascorbate-glutathione cycle and glyoxalase system

Abstract: The protective role of exogenously applied kinetin (10 μM KN, a cytokinin) against the adverse effects caused by NaCl-induced (150 mM) stress in Solanum lycopersicum was investigated. Application of KN significantly enhanced growth and biomass production of normally grown plants (non-stressed) and also mitigated the adverse effect of NaCl on stressed plants to a considerable extent. Among the examined parameters, chlorophyll and carotenoid contents, photosynthetic parameters, components of the antioxidant syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 90 publications
(124 reference statements)
19
102
0
Order By: Relevance
“…Increased antioxidant functioning due to NO application prevents the oxidative effects on the structure and function of chloroplast thylakoids [17]. In the present study, NO-mediated enhancement in the APX and GR activities and synthesis of AsA and GSH reflects in improved electron transport through maintenance of NADP [12]. Such effects of exogenous SNP were evident as increased photosynthetic rate.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Increased antioxidant functioning due to NO application prevents the oxidative effects on the structure and function of chloroplast thylakoids [17]. In the present study, NO-mediated enhancement in the APX and GR activities and synthesis of AsA and GSH reflects in improved electron transport through maintenance of NADP [12]. Such effects of exogenous SNP were evident as increased photosynthetic rate.…”
Section: Discussionsupporting
confidence: 48%
“…Compared to Ni-stressed and control, SNP-treated exhibited declined accumulation of MG, thereby preventing the possible toxic effects of MG on cellular stability. Earlier upregulation of glyoxalase-I due to kinetin [12] and NO [9] application has been demonstrated to mitigate salinity and cadmium mediated growth decline. However, reports discussing the effect of SNP on glyoxalase under Ni stress are not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ahanger et al . ). Studies have confirmed that Na + competes with K + for binding sites, thus reducing the uptake and accumulation of K + in plants (Hasegawa ).…”
Section: Introductionmentioning
confidence: 97%
“…The damaging effects of Cd at physiological and biochemical levels have been largely attributed to the excessive generation of ROS resulting in protein degradation, nucleic acid damage, photoinhibition, and membrane damage [5][6][7]. Indigenously occurring tolerance mechanisms that include the antioxidant system, the accumulation of compatible osmolytes, and secondary metabolites are employed to counteract the damaging effects of stresses [6,8].The antioxidant system is comprised of enzymatic and non-enzymatic components [9,10]. Efficient working of the antioxidant system, osmolyte, and secondary metabolite metabolism results in the quick elimination of ROS from different cellular components for better stress amelioration and growth maintenance [2,10].…”
mentioning
confidence: 99%